Intervention assessment of oral health literacy promotion of children's parents in Nanshan District of Shenzhen - LI Xue-qi; CHEN Si-han; YU Hong-bing; ZHANG Ting (口腔疾病防治, 2016)
Objective To assess the effectiveness of interactive workshop intervention measures between children and parents inonimproving oral health literacy of parents and oral health behavior of children. Methods We compared OHL and OHB score were compared among intervention group (A), parallel control group (B) and control group (C) before and after intervention. Results Compared with baseline, parents’ OHL score (t=22.369, P<0.001) and OHB scores (t=31.100, P<0.001) of intervention group were significantly increased 3 months later. Whereas parents’ of parallel control group (OHL: t=1.892, P=0.061; OHB: t=1.965, P=0.052), blank control group (OHL: t=1.56, P=0.120; OHB: t=1.591, P=0.114) had no significant changes.there were statistically significant differences among 3 groups of parents’ OHL (F=131.590, P<0.001) and OHB score (F=203.784, P<0.001) . Pairwise comparisons.There were statistically significant differences (P<0.001) between OHL and OHB before and after the intervention. Conclusion Interactive workshops intervention between children and parents can promote parental OHL and children oral health care greatly.